Social context modulates digestive efficiency in greylag geese (Anser anser) - Frigerio, Didone; Kotrschal, Kurt; Fabro, Carla; Puehringer-Sturmayr, Verena; Iaiza, Lara; Hemetsberger, Josef; Mason, Federico; Sarnataro, Chiara; Filacorda, Stefano (Scientific Reports, 2018)
In group-living animals, social context is known to modulate physiology, behaviour and reproductive output as well as foraging and nutritional strategies. Here we investigate the digestive efficiency of 38 individuals belonging to different social categories of a semi-feral and individually marked flock of greylag geese (Anser anser). During 9 consecutive days in winter 2017, when the ground was fully covered with snow (i.e. no grass or other natural forage available) and the accessible food was standardized, 184 individual droppings were collected and analysed to estimate the apparent digestibility of organic matter (ADOM). Lignin was used as an indigestible internal marker in the food and droppings. The digestive efficiency was higher in pairs with offspring as compared to pairs without offspring or unpaired birds. Furthermore, individuals with high ADOM were more likely to breed successfully in the following season than those with low ADOM. Our findings demonstrate that social status modulates digestive efficiency, probably via a chain of physiological mechanisms including a dampened stress response in individuals enjoying stable social relationships with and social support by their family members (i.e. their own pair-partner and offspring). Our findings underline the importance of the social network in modulating physiology, such as digestive efficiency, and ultimately reproductive success.